2021
DOI: 10.1021/acsomega.0c05054
|View full text |Cite
|
Sign up to set email alerts
|

Rosuvastatin Attenuates Rheumatoid Arthritis-Associated Manifestations via Modulation of the Pro- and Anti-inflammatory Cytokine Network: A Combination of In Vitro and In Vivo Studies

Abstract: The current investigation employed rosuvastatin for evaluation as an antiarthritic agent by in vitro and in vivo studies. In vitro studies comprised egg albumin and bovine serum albumin protein denaturation assays along with membrane stabilization assays, while in vivo studies comprised formaldehyde and complete Freund’s adjuvant (CFA)-provoked arthritis. The antioxidant potential was estimated via DPPH free radical scavenging and ferric reducing assays. Rosuvastatin significantly inhibited heat-provoked prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 41 publications
2
12
0
Order By: Relevance
“…In the present study, the DN group also showed high expression of renal TNF-α, signifying the stimulation of inflammatory pathway and cytokine production, which was ameliorated by RSV administration. This is in line with the reported anti-inflammatory effect of RSV decreasing TNF-α in diabetic nephropathy [ 45 ], LPS-induced cardiac injury [ 46 ] and rheumatoid arthritis animal models [ 47 ]. Apoptosis in renal tissue, in the current study, was also seen after the induction of DN, as indicated by increased renal expression of the pro-apoptotic protein, caspase 3, which was reversed by RSV administration.…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, the DN group also showed high expression of renal TNF-α, signifying the stimulation of inflammatory pathway and cytokine production, which was ameliorated by RSV administration. This is in line with the reported anti-inflammatory effect of RSV decreasing TNF-α in diabetic nephropathy [ 45 ], LPS-induced cardiac injury [ 46 ] and rheumatoid arthritis animal models [ 47 ]. Apoptosis in renal tissue, in the current study, was also seen after the induction of DN, as indicated by increased renal expression of the pro-apoptotic protein, caspase 3, which was reversed by RSV administration.…”
Section: Discussionsupporting
confidence: 88%
“…In the onset of RA, genetic composition and smoking are the predominant risk factors, and RA is diagnosed by clinical and laboratory assessments. In the diagnosis of RA, a combination of autoantibodies, i.e., rheumatoid factors (RF), anticitrullinated protein/peptide antibody (ACPA), C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), and X-ray imaging are frequently used. Research studies have reported that inflamed synovial fibroblasts play a major role in RA pathogenesis by stimulating the synthesis of proinflammatory mediator molecules. Mitogen-activated protein kinases (MAPK) and nuclear factor-κB are the main proinflammatory signalling pathways that mediate the expression of inflammatory molecules …”
Section: Introductionmentioning
confidence: 99%
“…8−10 Mitogen-activated protein kinases (MAPK) and nuclear factor-κB are the main proinflammatory signalling pathways that mediate the expression of inflammatory molecules. 11 Collagen-induced arthritis (CIA) is an excellent model for RA as it has helped to know and reveal pathogenic perspectives of autoimmune disease. It is critical to know about the distinct types of cells and their roles in the development of CIA and to test and develop novel therapeutic approaches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The discovery of novel biologics such as tofacitinib, infliximab, sarilumab, rituximab, and tocilizumab as a result of the comprehensive genetic analysis of RA disease has led to the development of more effective treatments. These medications have the ability to interfere with immune system components that are primarily responsible for tissue and joint inflammation (Kumar, Dhaliwal, et al., 2020; Qasim et al, 2021). But few reports showed that patients who received the above treatment were more prone to soft tissue, skin, respiratory, joint/bone, and genitourinary infections as compared with the herbal drugs.…”
Section: Introductionmentioning
confidence: 99%